Morphological diversity of tadpoles of fork-tongued frogs (Anura: Dicroglossidae) with different trophic specializations - Anna B. Vassilieva; Trung Duc Nguyen; Pavel A. Sorokin (Vertebrate Zoology)
Abstract Dicroglossid tadpoles are an important element of pond and stream communities in Southeast Asia. They are often found in syntopy but belong to different trophic guilds, from generalized detritophages to specialized predators. In the present research, the external and internal larval morphologies of seven anuran species of the family Dicroglossidae distributed in Vietnam (Fejervarya limnocharis, Fejervarya moodiei, Hoplobatrachus rugulosus, Limnonectes dabanus, Occidozyga lima, Occidozyga martensii, and Quasipaa verrucospinosa) are described and compared. An integrated approach is followed in the study by describing external and mouthparts morphologies, gross structure of the digestive tract, and the structure of chondrocranium and hyobranchium, which revealed the main trophic adaptations of tadpoles. Different trends in the evolution of larval macrophagy in Dicroglossidae led to the formation of fundamentally different larval forms. In the first case, the tadpoles are opportunistic predators that retain the ability to use a wide range of food resources (Hoplobatrachus); they have extremely specialized mouthparts but moderately transformed digestive tract and larval skeleton. In the other case, tadpoles are highly specialized obligate carnivores (Occidozyga) that have completely lost omnivory, with a radically transformed digestive tract, chondrocranium and hyobranchium. A comparison with generalized tadpoles revealed that in dicroglossids, the transformations of the larval skeleton due to carnivory mainly affect the labial cartilages and the palatoquadrate cartilage, as well as the hyobranchium. These transformations are common to macrophagous tadpoles of different taxonomic groups and result in greater larval morphological diversity.